The effect of standard heat and filtration processing procedures on antimicrobial activity and hydrogen peroxide levels in honey - Chen, Cuilan; Campbell, Leona; Blair, Shona E.; Carter, Dee A. (Frontiers in Microbiology, 2012)
There is increasing interest in the antimicrobial properties of honey. In most honey types, antimicrobial activity is due to the generation of hydrogen peroxide (H2O2), but this can vary greatly among samples. Honey is a complex product and other components may modulate activity, which can be further affected by commercial processing procedures. In this study we examined honey derived from three native Australian floral sources that had previously been associated with H2O2-dependent activity. Antibacterial activity was seen in four red stringybark samples only, and ranged from 12 to 21.1% phenol equivalence against Staphylococcus aureus. Antifungal activity ranged from MIC values of 19–38.3% (w/v) against Candida albicans, and all samples were significantly more active than an osmotically equivalent sugar solution. All honey samples were provided unprocessed and following commercial processing. Processing was usually detrimental to antimicrobial activity, but occasionally the reverse was seen and activity increased. H2O2 levels varied from 0 to 1017 μM, and although samples with no H2O2 had little or no antimicrobial activity, some samples had relatively high H2O2 levels yet no antimicrobial activity. In samples where H2O2 was detected, the correlation with antibacterial activity was greater in the processed than in the unprocessed samples, suggesting other factors present in the honey influence this activity and are sensitive to heat treatment. Antifungal activity did not correlate with the level of H2O2 in honey samples, and overall it appeared that H2O2 alone was not sufficient to inhibit C. albicans. We conclude that floral source and H2O2 levels are not reliable predictors of the antimicrobial activity of honey, which currently can only be assessed by standardized antimicrobial testing. Heat processing should be reduced where possible, and honey destined for medicinal use should be retested post-processing to ensure that activity levels have not changed.